Partisipasi Masyarakat dalam Manajemen Sarana dan Prasarana SDN 05 Cakranegara Pelajaran 2021/2022 - Rizca Ayu Widyasari (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The aim of the research is to evaluate citizen participation in performing educational infrastructure quality improvement program in SDN 05 Cakranegara. The methods used in analyzing the research are qualitative analysis, quantitative analysis and frequency distribution analysis. Qualitative analysis is used to identify the programs performed in SDN 05 Cakranegara, identify the educational infrastructures in SDN 05 Cakranegara, and identify the citizen participation in SDN 05 Cakranegara. The results of the analysis is the outsanding form of citizen participation is expressing advice and suggestion. And the rung of participation referring to Arnstein tipology is in placation category. In this fifth ladder, placation means that the society already has the influence although in some ways are still made by powerholders to judge the legitimacy of the advice. The data of the respondents are mostly male, 40-50 years old, postgraduates, teacher/lecture as well as enteprenuer and well-earned.